التقاضي الضريبي كضمانة دستورية للمكلف بدفع الضريب - محمد محمد علوم; خضير سولاف فيصل (Journal of Legal Sciences, 2019)
In this study we address in detail a collection of constitutional principles and rights directly to tax affairs i.e. the principles of tax legality , the right of tax equality and tax justice ,the right of prosecution within the valid 2005 constitution of the republic of Iraq the and the comparative constitutions. Despite the difference between them in the level and size of these rights and principles ,they all are guaranteed and maintained by them, yet the Iraqi tax laws came with many violations , penetrations and aggression on those principles and right such as the Iraqi income tax law no.113 for the year 1982 as amended, so we have to call the Iraqi taxation legislator to amend this law in the form that eliminates all these violations and returns back its constitutional character which it lost for a long period of time. Taxes are one of important financial policy instruments through which the state endeavors to provide the financial revenues necessary to finance its public expenditures as well as using them in directing the economy in the way targeted by the state for the purpose of achieving the economy and stability. Although Iraq is one of the most ancient state in the region in issuing tax legislations and law, the role of these legislations and law in financing the state’s expenditures and achieving its economic and social goals is limited in view of Iraq.